Implementasi Algoritma Hash-Based Dalam Mengetahui Pola Penjualan Obat - Berto Nadeak; Maringan Sianturi (BEES: Bulletin of Electrical and Electronics Engineering, 2022)
The development of technology can make it easier for us to carry out drug sales transactions. In carrying out marketing activities every day, you can make more and more data, because this data does not only function as an archive for a company. This data can be used and processed to produce information that will increase drug sales at Awiga pharmacies. The problem that often occurs in awiga pharmacies is not paying attention to drug stocks so that the drugs consumers want are not available or run out. Awiga Pharmacy does not utilize existing transaction data. So with that we need a data, namely data mining in order to be able to solve existing problems. In data mining, a method is needed. In this study, the authors used the hash-based method to make it easier for the authors to find out drug sales patterns. Based on the application in data mining using the hash based method with the title Implementation of the Hash-Based Algorithm in Knowing Drug Sales Patterns so as to get frequent 3-itemset results consisting of (Mefenamic Acid, Astemizole, Bisakodil Supp), (Mefenamic Acid, Astemizole, Bromhexin) , (Paracetamol, Diflucortolen, Ekanazol), (Paracetamol, Diflucortolen, Bisacodil Supp), (Bromhexin, Astemizole, Mefenamic Acid), and (Mefenamic Acid, Bisacodil Supp, Astemizole) each address 3-itemsest has the same support count value that is 2.